Ricardo's Use of Facts (Quarterly Journal of Economics, 1887)
Journal Article Ricardo's Use of Facts Get access The Quarterly Journal of Economics, Volume 1, Issue 4, July 1887, Pages 474–476, https://doi.org/10.1093/qje/1.4.474 Published: 01 July 1887